Parameters of Mineral Water that is Safe for Health - Issalillah, Fayola; Khayru, Rafadi Khan; Aisyah, Nur (Bulletin of Science, Technology and Society, 2022)
Water is a very valuable material in the life cycle and needs of everyday life, especially to be consumed as mineral water. Mineral water is stated to be health-safe if it fits the standards. The quality of mineral water must also be the best for health by being constantly monitored and evaluated. This paper reviews mineral water itself and its sources, parameters, processing steps, and quality management-controlling.